2011
DOI: 10.1007/s12603-011-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of dairy consumption and functional disability in older persons

Abstract: Frequent milk and milk products consumption is inversely associated with IADL disability in older men. Further research is needed to ascertain the protective effect of dairy products consumption on functional disability in older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…In line with this, previous studies have documented the relationship between food intake and functional disability such as dressing, bathing, eating, and other activities [44,45,46,47]. Studies on elderly Koreans proposed that frequent consumption of dairy products, legumes, or soy products were inversely related with functional disability [45,47].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In line with this, previous studies have documented the relationship between food intake and functional disability such as dressing, bathing, eating, and other activities [44,45,46,47]. Studies on elderly Koreans proposed that frequent consumption of dairy products, legumes, or soy products were inversely related with functional disability [45,47].…”
Section: Discussionmentioning
confidence: 64%
“…The relationship between food insecurity and QOL is complicated, because QOL is composed of multilateral factors such as exercise ability, self-management, daily activities, pain/discomfort, and anxiety/depression. However, some previous studies suggested that food insecurity may affect some factors of QOL, like exercise ability and daily activity, through low-quality food intake, essential nutrient deficiencies, and poor nutritional status [45,46,47,48,49,50]. In our study, we found that the “food-insecure household” groups, particularly the “food-insecure household with hunger” group generally showed higher proportions of energy and nutrient deficiencies when compared with the 2015 KDRIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed information has been published elsewhere [22,23]. In addition, a qualitative food frequency questionnaire (FFQ) with 63 common food items was used to get the diet information [24]. The FFQ had 10 frequency responses such as almost never, 6-11 times per year, once per month, 2-3 times per month, once per week, 2-3 times per week, 4-6 times per week, once per day, 2 times per day, and 3 times per day.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found positive effects of dairy consumption in elderly people, but the evidence base for this recommendation remains scarce. One study found that daily consumption of milk and milk products was inversely associated with functional disability in older men . Another found that women who consumed dairy products had greater whole‐body lean mass and better physical performance than those who did not .…”
mentioning
confidence: 99%